2013
DOI: 10.4236/ojrd.2013.32012
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic and Prognostic Value of Serum Procalcitonin among Ventilator Associated Pneumonia Patients*

Abstract: Ventilator-associated pneumonia (VAP) is a complication in as many as 28% of patients who receive mechanical ventilation. Studies have consistently shown that a delay in diagnosis and treatment increases the mortality risk. The aim of this work was to clarify the role of the serum procalcitonin (PCT) in the diagnosis and the prognosis of ventilator associated pneumonia. Methods: Forty two VAP patients, 20 non VAP-ICU (on mechanical ventilation) admitted patients and 20 healthy control subjects of similar age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…3 ). The authors concluded that the increase of serum procalcitonin is an important diagnostic marker in identifying and predicting the outcome of VAP, and its usefulness is confirmed by the result of many other studies ( 23 , 24 , 25 ).…”
Section: Diagnostic Importance Of Procalcitoninmentioning
confidence: 78%
See 3 more Smart Citations
“…3 ). The authors concluded that the increase of serum procalcitonin is an important diagnostic marker in identifying and predicting the outcome of VAP, and its usefulness is confirmed by the result of many other studies ( 23 , 24 , 25 ).…”
Section: Diagnostic Importance Of Procalcitoninmentioning
confidence: 78%
“…Clinical symptoms and chest radiogram in the first phase of VAP development are not typical, and etiological significance of microbial isolates from tracheobronchial secretion is questionable, with regard to the expected colonization of respiratory pathogens. El Halim et al ( 23 ) compared the mean values of PCT in the group of VAP-patients (n = 42), with values in patients on mechanical ventilation without VAP (n = 20) and control group of healthy patients (n = 20). They demonstrated a significantly higher PCT values (p <0.001) in the VAP group (1.54 ± 0.50 ng / ml), compared to patients without VAP (0.06 ± 0.03 ng / ml) and patients of control group (0.04 ± 0.02 ng / ml) (Fig.…”
Section: Diagnostic Importance Of Procalcitoninmentioning
confidence: 99%
See 2 more Smart Citations
“…• It is used for assisting the prognosis of severe localised infections such as pneumonia [19] • In critically ill patients with systemic infection helps in explaining the prognosis • As well as in starting antibiotics in case of elevated PCT, its normal level can guide us to discontinuing antibiotics, this will reduce antibiotic use and help in antimicrobial stewardship. [20] PROGNOSTIC VALUE OF PCT…”
Section: Some Of the Proposed Applications Arementioning
confidence: 99%